Microbial associations and transfers across the One Health Triad effects on human and animal adiposity and temperament: a protocol for an observational pilot study - Zeigler, Mariah K.; Vander Wyst, Kiley B. (Frontiers in Public Health, 2023)
Introduction It is known that humans and pet dogs harbor microbial communities that are important regulators of health and disease. Pet dogs have been shown to promote microbial exchange between members of a household, a process that may have lasting health implications. Infancy marks a unique period of development as environmental exploration and introduction to complementary foods occur. This may lead to greater opportunities for microbial transfer between pet dogs and human infants due to a more confined shared environment, similar means of mobility, greater physical contact, and increased frequency of shared foods. This human-animal bond has led to extensive research in the areas of childhood allergies and behavioral health; however, there is a paucity in the available literature that has evaluated how this unique ecological relationship may impact both human and animal health. Methods Infants who reside in a household with a pet dog will be recruited from the greater Phoenix metropolitan area for this longitudinal, observational pilot study and followed through the complementary feeding period. Infant and pet dog fecal, salivary, and skin samples, as well as environmental samples from feeding areas/surfaces and main indoor play areas from both infants and pet dogs will be collected through in-home visits before (~5 mos), during (~9 mos), and after (~12 mos) the complementary feeding (CF) period. Anthropometrics, temperament, and dietary habits of both infants and pet dogs along with assessment of the home condition will also be collected. Microbial comparisons between infant and pet dog samples and evaluation of microbial changes during the CF period will be evaluated. Further, we will assess relationships between microbial composition and adiposity and temperament of both infants and pet dogs. Discussion The proposed observational pilot study will advance the available science by exploring how microbial communities are associated and change between infants and pet dogs before, during, and after the CF period, a unique period of human growth and development. Findings from this study will provide insights into the impact these ecological relationships have on each other and how transfer across the One Health Triad impacts human and animal health.